Microlepidogaster negomata, a new hypoptopomatine catfish (Loricariidae: Hypoptopomatinae) from Rio São Francisco basin, southeastern Brazil - Martins, Fernanda O.; Cherobim, Arieli M. [UNESP]; Andrade, Breno N. [UNESP]; Langeani, Francisco [UNESP] (Magnolia Press, 2017)
The number of species of Microlepidogaster recently increased considerably, the genus presently comprises six species distributed in the Paraná, São Francisco, and Jequitinhonha river basins. A new species of Microlepidogaster is herein described from the upper Rio São Francisco basin, which can be distinguished from all congeners by having two exclusive features within the genus: skin over swimbladder opening with two to five reduced unperforated platelets, and ventral laminar expansion of coracoid enclosing completely or almost completely the arrector fossa of the pectoral girdle. In addition, other features to recognize this species are: snout covered by many small plates bearing slender pointed odontodes; presence of iris operculum; exposure of pectoral girdle restricted to the lateral portion; presence of pectoral axillary slit only in juveniles; anterior portion of compound supraneural plus first dorsal-fin proximal radial contacting the neural spine of the eighth or ninth vertebra; first anal-fin pterygiophore covered only by skin; and uninterrupted, long median and middorsal series of lateral plates.
Keywords: Biodiversity; Cascudinhos; Freshwater fish; Neotropical; Taxonomy; Teleostei